Investigation of Thermomorphogenesis-Related Genes for a Multi-Silique Trait in Brassica napus by Comparative Transcriptome Analysis - Chai, Liang; Zhang, Jinfang; Li, Haojie; Cui, Cheng; Jiang, Jun; Zheng, Benchuan; Wu, Lintao; Jiang, Liangcai (Frontiers in Genetics, 2021)
In higher plants, the structure of flower is precisely controlled by a series of genes. Aberrance flower results in abnormal fruit morphology. Previously, we reported a multi-silique rapeseed (Brassica napus) line zws-ms. We identified two associated regions and investigated differentially expressed genes (DEGs), thus some candidate genes underlying the multi-silique phenotype in warm area Xindu were selected. However, this phenotype was switched off by lower temperature, and the responsive genes, known as thermomorphogenesis-related genes, remained elusive. So, based on that, in this study, we further investigated the transcriptome data from buds of zws-ms and its near-isogenic line (NIL) zws-217 grown in colder area Ma’erkang, where both lines showed normal siliques only, and analyzed the DEGs between them. Totally 117 DEGs were then detected, among which 33 of them represented the same or similar expression trends with those from Xindu; while the other 96 DEGs showed different expression trends and they were defined as environment-specific. Furthermore, we combined this with the gene annotations and ortholog information, and then selected BnaA09g45320D (chaperonin gene CPN10-homologous) and BnaC08g41780D (Seryl-tRNA synthetase gene OVA7-homologous) the most possible thermomorphogenesis-related genes, which probably switched off the multi-silique under lower temperature. This study paves a way to a new perspective into flower/fruit development in Brassica plants.